(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The frontiers reached by gene editing and their applications for animals, plants and humans raise numerous tricky issues, posing new and renewed challenges for constitutional law scholars. This paper focuses on the role that the public can play in decision-making processes aimed at regulating gene-editing technologies. Thus, it reflects on the opportunity to develop and enhance deliberative arenas, which guarantee a fuller participation of citizens in legislative choices that touch upon controversial scientific issues of general interest, in compliance with the principles of deliberative democracy.